2002
DOI: 10.1248/cpb.50.964
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Biatractylolide, an 8,8' (C-C) Linked Dimeric 12,8-Eudesmanolide from the Resin of Trattinickia rhoifolia WILLD.

Abstract: In previous papers 1,2) we have described several compounds, mainly sesquiterpenoids, isolated from the resin of Trattinickia rhoifolia WILLD. (Burseraceae). In this paper we report the isolation and structure elucidation by spectroscopic methods and X-ray diffraction analysis of biatractylolide (1). Results and DiscussionTo the solution of resin of T. rhoifolia in methylene chloride, n-hexane was added to selectively precipitate and separate the insoluble material; the soluble part was taken to dryness and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…A voucher specimen of A. ovata (AO‐1013) was deposited in the Graduate Institute of Pharmacognosy Science, Taipei Medical University. The isolation procedure was modified from a previous study 20,21 . Evidence has shown that the major active components of A. ovata were sesquiterpenoids.…”
Section: Methodsmentioning
confidence: 99%
“…A voucher specimen of A. ovata (AO‐1013) was deposited in the Graduate Institute of Pharmacognosy Science, Taipei Medical University. The isolation procedure was modified from a previous study 20,21 . Evidence has shown that the major active components of A. ovata were sesquiterpenoids.…”
Section: Methodsmentioning
confidence: 99%
“…153 It was interesting that biatractylolide 152 was also found to be present in the resin of Trattinickia rhoifolia. 154 Biologically, biatractylolide possesses negative inotropic and chronotropic actions on isolated guinea pig hearts -specifically, it significantly inhibited the contractile force and decreased the heart rate of the isolated right atrium, making it a potential agent for lowering blood pressure. 155 The biomimetic synthesis of these dimers has been reported.…”
Section: Eudesmane and Elemane Sesquiterpenoid Dimersmentioning
confidence: 99%
“…Scheme 11 Biatractylolide (86) is a symmetrical dimeric sesquiterpenoid from the resin of Trattinickia rhoifolia Willd. [59]. Glochidiolide (87) is a dimeric butenolide isolated from the leaves of Glochidion acuminatum Mˇll.…”
mentioning
confidence: 99%